An Analysis of SWOT on The Development of Marketing Strategies of J&T Express Service Companies - Ajeng Alifah, Fajrina (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
This article discusses the development of marketing strategies for J&T Express, a delivery service company. Through the use of technology, improved customer service, promotional campaigns, network expansion, and optimization of operational processes, the company aims to improve customer experience, expand market reach, and optimize its operational efficiency. By focusing on innovation and customer satisfaction, J&T Express strives to maintain its position as a leader in the logistics industry.